Atualização de ERP: um estudo de caso em uma empresa do setor atacadista do nordeste paraense - COSTA, Matheus Natividade (2022)
The Preço Ótimo chain is a Brazilian wholesale-retail supermarket chain belonging to the famous Preço Top group. Besides Brazil, the model has been exported to countries in South America and Europe. Some units also offer gas station and drugstore services. Its operations in Brazil are in all Brazilian states and in the Federal District. It has more than 240 self-service stores and more than 30 wholesalers/distribution centers spread throughout Brazil. In face of all this growth and expansion, it became necessary to update the sales ERP (Enterprise Resource Planning) used, because it had been running for more than 30 years, making use of old and outdated technologies. This work aims to document this change, identifying the main reasons that led to this change, the challenges faced by users, and the results obtained, whether negative or positive. The theme of this work was chosen due to the author's familiarity with it, as he was able to closely follow the entire updating process of the system addressed, besides the fact that it will contribute to the process of future updates of other systems. The names Preço Ótimo and Preço Top, and of the target systems TopSys and TopSys Web, are fictitious names in order to preserve the true identity of the company that is the focus of the study.